Looking for a loopholes in power asymmetry: public engagement in Slovak countryside in intersectional perspective - Hájková, Kristýna (Romano džaniben, 2020)
The article deals with the ways and limits of participation in public life in a Slovak village, where one third of population is Roma. The main theoretical concept is intersectional theory, which is used to analyse how categories of gender and ethnicity influence access to power in local government participation and societies engagement. The division of the village on the basis of ethnicty is very noticeable in this research field, so gender, which is fundamental and omnirelevant cathegory, seems like invisible. It is difficult for Romanies to take part in the local government and societies because of mechanisms of opression, but it does not prevent them from complete participation in public life. Especially Romani women were able to find a loophole in mechanisms of oppression and they based their public activities on informal relationships. They influence the public affairs in their village, despite of having only limited possibilities and their public engagement is still limited externally. Incorporation gender cathegory into analysis makes possible to desribe the structural barriers whose Romani women face, and also the mechanisms of opression, whose seemingly cover even the fundamenetal gender cathegory.